2011
DOI: 10.18352/jsi.246
|View full text |Cite
|
Sign up to set email alerts
|

How social workers experience supervision: results of an empirical study in the healthcare sector

Abstract: A B S T R A C T How social workers experience supervision: results of an empirical study in the healthcare sectorVery few studies provide insights into how social workers experience supervision as a means of supporting their professional working relations with medical doctors and nurses. The research findings presented in this paper are based on an extensive quantitative survey on "Knowledge and Expertise" in everyday work settings, and guided interviews conducted with selected respondents throughout Germany. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…The results also show a wider difference between supervision of health social workers and statutory social workers than the minor differences found by Scott and Farrow (1993). The results of this survey are markedly different from the ambivalence reported in the German study of supervision within health settings and the lack of participation in clinical supervision reported in the Ontario study (Geißler-Piltz, 2011;Sewell et al, 2021). The NGO supervision findings show a more positive experience of supervision than those reported in the comparative UK and Australian study (Robinson, 2013).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The results also show a wider difference between supervision of health social workers and statutory social workers than the minor differences found by Scott and Farrow (1993). The results of this survey are markedly different from the ambivalence reported in the German study of supervision within health settings and the lack of participation in clinical supervision reported in the Ontario study (Geißler-Piltz, 2011;Sewell et al, 2021). The NGO supervision findings show a more positive experience of supervision than those reported in the comparative UK and Australian study (Robinson, 2013).…”
Section: Discussioncontrasting
confidence: 76%
“…In the last decade, there has been specific research about supervision in child welfare, health and NGO settings ( Geißler-Piltz, 2011;McPherson et al, 2016;Rankine et al, 2018;Robinson, 2013;Sewell et al, 2021;Wilkins et al, 2017). British research about child welfare supervision has identified what happens in supervision, how it is recorded, a lack of time and space for reflection and supervision having primarily a managerial focus ( Beddoe et al, 2021;Saltiel, 2017;Wilkins et al, 2017).…”
Section: Introductionmentioning
confidence: 99%